ANALYSIS MARKETING DISTRIBUTION OF SEEDS GURAMI FISH (Osprhonemus gouramy) IN GROUP FISH CULTIVATION INGIN MAJU, KECAMATAN LUAK, LIMA PULUH KOTA DISTRICT, SUMATERA BARAT PROVINCE - Muthiya Lastri; Lamun Bathara; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Marketing Distribution of Gouramy Seeds (Osprhonemus gouramy) in Group Fish Cultivator Ingin Maju, Kecamatan Luak, Lima Puluh Kota District, Sumatera Barat Province.This research was conducted from March to April 2019.The method used is the survey method by conducting observations directly into the field by collecting data through interviews based on questionnaires, determining respondents using purposive sampling and snowball sampling as many as 34 respondents fishermen, while respondents marketing institutions as many as 3 collectors, 1 wholesaler and 3 retailers.Based on the results of the study it can be explained that gouramy seeds (osprhonemus gouramy) size of 1 inch marketing channel is economically efficient, seen from the farmer's share value of more than 50%, which is 65%, and the marketing margin value of IDR. 1330 per head. Marketing channel 2 is also an economically efficient marketing channel, seen from the farmer's share value of more than 50%, which is 65% and the marketing margin value of IDR. 982 per head. Marketing channel 1 is a marketing channel that is less economically efficient, seen from the farmer's share value of less than 50%, which is 30% and the marketing margin value of IDR. 1110 per head. For gouramy seeds 2 inch size economically efficient marketing channel, seen from the farmer's share value of more than 50%, namely 53.47%, and the marketing margin value of IDR. 1552 per head. Marketing channel 2 is also an economically efficient marketing channel, seen from the farmer's share value of more than 50%, which is 53.47% and the marketing margin value of IDR. 1962 per head. Marketing channel 3 is an economically efficient marketing channel, seen from the farmer's share value of more than 50%, which is 53.47% and the marketing margin value of IDR. 1332 per head. While the gouramy seeds 3inch size of the marketing channel is economically efficient, seen from the farmer's share value of more than 50%, which is 63.08%, and the marketing margin value of IDR. 2022 per head. Marketing channel 2 is also an economically efficient marketing channel, seen from the farmer's share value of more than 50%, which is 63.08% and the marketing margin value of IDR. 2022 per head. Marketing channel 1 is an economically efficient marketing channel, seen from the farmer's share value of more than 50%, which is 63.08% and the marketing margin value of IDR 1802 per head. Keywords: Gourami Fish Seeds, Marketing Channels, Marketing Margin